Zero-waste Culture in Sustainable Ethnopedagogy in Surabaya for SDG 12's Goals of Responsible Consumption and Production - Solihin, Annas; Gunansyah, Ganes; Mariana, Neni; Nursalim, Mochamad; Julianto, Julianto (Jurnal Pendidikan Edutama, 2025)
This study examines the implementation of a zero-waste culture through sustainable ethnopedagogy as a contribution to achieving SDG 12’s goals in Surabaya, focusing on Citraland Fresh Market, Dinoyo Keputran Waste Bank, and Keputran I Elementary School. Using a qualitative, descriptive-analytical approach, data were collected through field observations, in-depth interviews, and documentation. The Citraland Fresh Market reduces single-use plastics and promotes responsible consumption, though behavioral changes among traders and consumers remain challenging. Dinoyo Keputran Waste Bank effectively manages waste at the community level, but infrastructure and participation require improvement. Keputran I Elementary School integrates sustainable ethnopedagogy via waste management projects, fostering cooperation and environmental awareness. The study concludes that collaboration among markets, waste banks, and schools strengthens local efforts toward SDG 12’s goals. Policy support and sustainable education are essential to ensure wider adoption and effectiveness of the zero-waste culture.